AWARENESS OF MEDICINAL APPLICATIONS OF PIPER NIGRUM AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Black pepper includes the many commonly used ingredients upon this planet, remarkable for some of its potent component piperine. White pepper is made with closely related species, while black pepper is prepared by fast processing and wind drying of underripe natural products, white pepper is made from dried, regular and ready mixed seeds. Piperine has been the conventional biologically active conjugate of Piper nigrum and Piper longum, having been taken into consideration for therapeutic effects..The purpose of this survey was for assessing the awareness of medicinal applications of Piper nigrum amongst dental students.A cross sectional survey was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about Piper nigrumtherapy in medical applications ,their immunomodulatory properties, anti pyretic properties,.anti spasmodic activity,anti inflammatory activity, and its mechanism of action and side effects. The responses were recorded and analysed.16% of the respondents were aware of the medical applications of Piper nigrum therapy .11 % were aware of the anti immunomodulatory activity of Piper nigrum therapy .9 % were aware of anti pyretic properties of Piper nigrum therapy .13 % were aware of anti spasmodic properties of Piper nigrum therapy .10 % were aware of anti inflammatory properties of Piper nigrum therapy . 6 % were aware mechanism of action and side effects of Piper nigrum therapy .The awareness about the use of Piper nigrum therapy in medicinal applications is low among dental students.Increased awareness programs and sensitization and continuing dental education programs along with greater importance to the curricular modifications can further enhance knowledge and awareness about Piper nigrum therapy.